IMPLEMENTING STEM PROJECT-BASED ONLINE SCIENCE LEARNING FOR PRE-SERVICE TEACHERS - Eko Yuliyanto; Muhamad Imaduddin; Monera A. Salic-Hairulla (Universitas Muhammadiyah Semarang, 2021)
This research is to analyze the interests, knowledge mastered and the application of 21st century skills in online STEM learning. This research is an action in implementing project-based learning with a STEM approach which is carried out with a Learning Management System (LMS), namely Schoology and assisted by other applications, namely Zoom Meeting and WhatsApp. The participants are pre-service chemistry teachers in the second year who are taking Integrated Science courses at the Muhammadiyah University of Semarang, Indonesia as many as 16 students. The research method used a qualitative approach to find out phenomena that arise and reveal from time to time. The data obtained in the form of answers to questionnaires, pictures of STEM project diagrams, STEM product videos and STEM product descriptions. It was found that the stage changes in online STEM learning were different when it was implemented in the offline condition. It was shown that the pre-service teachers were interested in working on STEM projects, increasing their knowledge and collaboration skills. The novelty of this study is the implementation of online STEM learning in the pandemic era by involving family members. Key words: STEM, Online Science Learning, Project-Based learning, Pre-service Teachers